Drag drop on high-speed supercavitating vehicles and supersonic submarines - Nesteruk, I. (Прикладна гідромеханіка, 2015)
Supercavitation can significantly reduce the drag of high-speed underwater vehicles. To be located inside the cavity, the shape of the hull varies at different operating velocities and becomes very slender at high speeds. Simple estimations showed that at steady horizontal motion, the drag of a properly shaped supercavitating vehicle of a given volume decreases with increasing speed. This drag reduction opens up prospects for designing large high-speed underwater vehicles and even supersonic submarines. Суперкавитация может существенно снижать сопротивление высокоскоростных подводных аппаратов. Для размещения корпуса внутри каверны его форма должна изменяться при разных скоростях движения и становится очень удлиненной на больших скоростях. Простые оценки показали, что при установившемся горизонтальном движении сопротивление соответственно сконструированного суперкавитирующего аппарата уменьшается при возрастании скорости. Это падение сопротивления открывает перспективы создания крупнотоннажных высокоскоростных подводных аппаратов и даже сверхзвуковых подводных лодок. Суперкавiтацiя може суттєво знизити опiр високошвидкiсних пiдводних апаратiв. Щоб корпус розташовувався всерединi каверни, його форма має бути рiзною при рiзних швидкостях руху i стає дуже видовженою на великих швидкостях. Простi оцiнки показали, що при усталеному горизонтальному русi опiр вiдповiдно сконструйованого суперкавiтуючого апарата фiксованого об’єму зменшується зi зростанням швидкостi. Це спадання опору вiдкриває перспективи створення великотоннажних високошвидкiсних пiдводних апаратiв i навiть надзвукових пiдводних човнiв.